In vitro profiling of the metabolism and drug–drug interaction of tofogliflozin, a potent and highly specific sodium-glucose co-transporter 2 inhibitor, using human liver microsomes, human hepatocytes, and recombinant human CYP. (March 2015) - Yamane, Mizuki; Kawashima, Kosuke; Yamaguchi, Koji; Nagao, Shunsuke; Sato, Mika; Suzuki, Masayuki; Honda, Kiyofumi; Hagita, Hitoshi; Kuhlmann, Olaf; Poirier, Agnes; Fowler, Stephen; Funk, Christoph; et al.
Abstract 1. The metabolism and drug–drug interaction (DDI) risk of tofogliflozin, a potent and highly specific sodium-glucose co-transporter 2 inhibitor, were evaluated by in vitro studies using human liver microsomes, human hepatocytes, and recombinant human CYPs. 2. The main metabolite of tofogliflozin was the carboxylated derivative (M1) in human hepatocytes, which was the same as in vivo. The metabolic pathway of tofogliflozin to M1 was considered to be as follows: first, tofogliflozin was catalyzed to the primary hydroxylated derivative (M4) by CYP2C18, CYP4A11 and CYP4F3B, then M4 was oxidized to M1. 3. Tofogliflozin had no induction potential on CYP1A2 and CYP3A4. Neither tofogliflozin nor M1 had inhibition potential on CYPs, with the exception of a weak CYP2C19 inhibition by M1. 4. Not only are multiple metabolic enzymes involved in the tofogliflozin metabolism, but the drug is also excreted into urine after oral administration, indicating that tofogliflozin is eliminated through multiple pathways. Thus, the exposure of tofogliflozin would not be significantly altered by DDI caused by any co-administered drugs. Also, tofogliflozin seems not to cause significant DDI of co-administered drugs because tofogliflozin has no CYP induction or inhibition potency, and the main metabolite M1 has no clinically relevant CYP inhibition potency.